Corporate Social Responsibility in Family Firms: Status and Future Directions of a Research Field - Christoph Stock; Laura Pütz; Sabrina Schell; Arndt Werner (Journal of Business Ethics, 2023)
This systematic literature review contributes to the increasing interest regarding corporate social responsibility (CSR) in family firms—a research field that has developed considerably in the last few years. It now provides the opportunity to take a holistic view on the relationship dynamics—i.e., drivers, activities, outcomes, and contextual influences—of family firms with CSR, thus enabling a more coherent organization of current research and a sounder understanding of the phenomenon. To conceptualize the research field, we analyzed 122 peer-reviewed articles published in highly ranked journals identifying the main issues examined. The results clearly show a lack of research regarding CSR outcomes in family firms. Although considered increasingly crucial in family firm research, a study investigating family outcomes (e.g., family community status, family emotional well-being), as opposed to firm outcomes, is missing. This literature review outlines the current state of research and contributes to the actual debate on CSR in family firms by discussing how family firms can use CSR activities as strategic management tools. Moreover, our analysis shows a black box indicating how CSR links different antecedents and outcomes. The black box is significant since firms generally need to know where to allocate their scarce resources to generate the best outcomes. We identify nine research questions based on these findings, which we hope will inspire future research.
Keywords: 300; Systematic Literature Review; Family Firms; Corporate Social Responsibility; Sustainable Family Business Theory; Antecedents; Outcomes